2019
DOI: 10.1111/jvim.15414
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors associated with development of clinical cardiotoxicity in dogs receiving doxorubicin

Abstract: Background Doxorubicin (DOX) can cause cumulative cardiotoxicity in dogs, but the incidence of clinical cardiotoxicity in dogs receiving DOX has not been determined. Hypothesis/Objectives To determine if the duration of DOX infusion influences the incidence of cardiotoxicity, to characterize the incidence of clinical cardiotoxicity in dogs during or after DOX chemotherapy, and to identify any risk factors associated with cardiotoxicity. Animals Four‐hundred ninety‐four dogs that received at least 1 dose of DOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
2
27
1
1
Order By: Relevance
“…Doxorubicin is frequently used in chemotherapy against acute leukaemia, malignant lymphoma, and several solid tumours. Although DOX has been frequently reported to exhibit minimal cardiotoxicity at a single dose, there is still a risk of cardiomyopathy when multiple doses are administered (Hallman et al, 2019). The pathophysiological mechanisms underlying doxorubicin-induced cardiotoxicity include three interrelated respects: accumulation of reactive oxygen species (ROS); dysfunction of topoisomerase IIβ and topoisomerase I; and mitochondrial imbalance of intracellular calcium (Burridge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin is frequently used in chemotherapy against acute leukaemia, malignant lymphoma, and several solid tumours. Although DOX has been frequently reported to exhibit minimal cardiotoxicity at a single dose, there is still a risk of cardiomyopathy when multiple doses are administered (Hallman et al, 2019). The pathophysiological mechanisms underlying doxorubicin-induced cardiotoxicity include three interrelated respects: accumulation of reactive oxygen species (ROS); dysfunction of topoisomerase IIβ and topoisomerase I; and mitochondrial imbalance of intracellular calcium (Burridge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in LVIDd and FS may indicate development of cardiomyopathy, with systolic dysfunction. Indeed, a recent study in dogs showed that a decrease in FS with DOX treatment was associated with the development of cardiac clinical signs 48 . The relationship between cardiac injury and these echocardiographic parameters is further confirmed by the correlations between LVEF and FS with increasing concentrations of cTnI.…”
Section: Discussionmentioning
confidence: 78%
“…This may explain why some dogs with B-cell lymphoma do not respond or partially respond to TOPIIa inhibitors. It is worth mentioning that cy-totoxic drugs can cause numerous side effects and in extreme cases can lead to the patient's death [16,40,44,51]. Unfortunately, despite the use of numerous lymphoma classifications, it is currently not possible, based solely on histopathological examination and the lymphoma immunophenotype, to determine the most effective therapy for individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the adverse reactions associated with the use of doxorubicin are observed. The most common is the cardiotoxicity that develops with long-term use and chemotherapy-induced myelotoxicity [14,40,51,53]. The possibility of determining in which patients the use of doxorubicin would be beneficial and in which its use would not bring satisfactory results ©Polish Society for Histochemistry and Cytochemistry Folia Histochem Cytobiol.…”
Section: Discussionmentioning
confidence: 99%